TINJAUAN YURIDIS BENTUK BADAN USAHA PERSEROAN TERBATAS BAGI PERUSAHAAN YANG DIDIRIKAN DALAM RANGKA PENANAMAN MODAL ASING - Retno Hendrati Purwaningrum (Perspektif, 2002)
The types of companies reegulated in UU no. 1/1995 and PP no. 20/1994 seems to be good instruments to attract foreign investors to conduct their activities in Indonesia. However, in accordance with concept ogf the social welfare state (as stated in Pancasila), the effect for Indonesia people itself should be taken more consideration.